PENGARUH GRASTON TECHNIQUE DAN CLOSED KINETIC CHAIN EXERCISE PADA OSTEOARTHRITIS KNEE DEXTRA - Kuswardani .; Fitratun Najizah; Nurma Oktaviani (Universitas Widya Husada Semarang, 2020)
Background : The prevalence of osteoarthritis in Indonesia increases with age. The highest prevalence is at age <75 years. The incidence of osteoarthritis in Indonesia from 1990 to 2010 has increased. Per 100,000 men and women reach their peak at the 80 years old. Women reached a peak at 1,327.4 compared to men who were only 907.7. Osteoarthritis of the knee has problems such as pain, decreased ROM, edema, and decreased muscle strength, to overcome the problems in the case of knee osteoarthritis can be given physiotherapy treatment such as Graston Technique and Closed Kinetic Chain Exercise. Objective : The purpose of this study was to determine the effect of graston technique and closed kinetic chain exercise on knee dextra osteoarthritis to overcome body and function. Results : After being given physiotherapy management with a combination of graston technique and closed kinetic chain exercise in patients with knee osteoarthritis, there was a decrease in pain so that the increase in functional ability is known from the reduction of the diagram from the results of filling the WOMAC index form pre treatment with the score being post treatment in six meetings. Conclusion : The combination of graston technique and closed kinetic chain exercise has effect on reducing pain so that it can improve the functional abilities of patients with knee osteoarthritis.